2015
DOI: 10.1108/jpif-01-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

The long-term linkages between direct and indirect property in Australia

Abstract: The authors study the linkages between direct and indirect Australian property sectors from 1985 to 2013, with shares and bonds. This paper employs an Autoregressive Fractionally Integrated Moving Average (ARFIMA) process to de-smooth a valuationbased direct property index. The authors establish directional lead-lag relationships between markets using bi-variate Granger causality tests. Johansen cointegration tests are carried out to examine how direct and indirect property markets adjust to an equilibrium lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…Following Oikarinen, Hoesli, & Serrano (2011) and Hoesli & Oikarinen (2012), we use the national stock market index as the proxy for common stocks. The choice of sample are also similar with recent and previous studies, such as in US and UK market (Hoesli & Oikarinen, 2012, 2016, Yong & Pham (2015) in Australia as well as in other international markets (Yunus, Hansz, & Kennedy, 2012).…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…Following Oikarinen, Hoesli, & Serrano (2011) and Hoesli & Oikarinen (2012), we use the national stock market index as the proxy for common stocks. The choice of sample are also similar with recent and previous studies, such as in US and UK market (Hoesli & Oikarinen, 2012, 2016, Yong & Pham (2015) in Australia as well as in other international markets (Yunus, Hansz, & Kennedy, 2012).…”
Section: Introductionsupporting
confidence: 79%
“…Before this, Mei & Lee (1994) and Geltner & Kluger (1998) (Morawski, Rehkugler, & Fuss, 2008;Sebastian & Schatz, 2009). Furthermore, similar tight long-run relationship between REITs and direct real estate occur in the other international market like Australia and Netherlands (Yong & Pham, 2015;Yunus et al, 2012). Oikarinen et al (2011) highlight the tight relationship between REITs and direct real estate exist since no cointegration between REITs and stocks in the long-run.…”
Section: Literature Reviewmentioning
confidence: 68%
See 2 more Smart Citations
“…Many research papers have identified a significant long-run relationship between REITs and direct real estate returns (Giliberto, 1990;Mei and Lee, 1994;Geltner and Kluger, 1998;He, 2000;MacKinnon and Al Zaman, 2009;Oikarinen et al, 2011;Yunus et al, 2012;Yong and Pham, 2015), with the latter paper studying Australian markets. These findings are consistent with general expectations of competitive markets, given the underlying composition of REITs consist of a portfolio of direct real estate itself.…”
Section: Introductionmentioning
confidence: 99%